Pre-Marital Education in Islam: An Analysis of Its Role in Preventing Divorce - Lalu Irawan Muda; Ulyan Nasri (Jurnal Ilmiah Profesi Pendidikan, 2024)
Marriage is a sacred institution in Islam aimed at building a family based on sakinah, mawaddah, wa rahmah (tranquility, love, and mercy). However, the high divorce rates in various Muslim countries indicate issues in couples’ preparedness for married life. Pre-marital education serves as a crucial instrument in providing prospective spouses with an understanding of their rights, obligations, and conflict resolution in the family according to Islamic law. This study aims to analyze the role of pre-marital education in preventing divorce and its effectiveness in strengthening family resilience. This research employs a qualitative method with a descriptive-analytical approach. Data collection techniques include literature studies, interviews with Islamic family law experts and pre-marital education providers, and document analysis of relevant policies. Data analysis follows the Miles and Huberman model, comprising data reduction, data presentation, and conclusion drawing.  The study results show that pre-marital education plays a significant role in enhancing couples’ understanding of effective communication, conflict management, and psychological and financial aspects of marriage. This program also contributes to raising awareness of the importance of commitment in marriage based on Islamic values. The study concludes that pre-marital education is an effective preventive measure in reducing divorce rates. Its implications suggest that governments and religious institutions should develop a more comprehensive and need-based pre-marital education curriculum for Muslim couples.